RELATIVE HUMADITY ESTIMATION BASED ON MODIS PRECIPITABLE WATER FOR SUPPORTING SPATIAL INFORMATION OVER JAVA ISLAND - Parwati Sofan; Totok Sugiharto; Hasnaeni (BRIN, 2007)
This research is performed to derive weather property, i.e. relative humidity, based on precipitable water from MODIS (Moderate Resolution Imaging Spectroradiometer) data which on board of TERRA/AQUA satellites. As one of dynamic atmospheric parameters, the precipitable water has ability to indicate the dryness or wetness of a certain area. It can be derived by MODIS at 0.865, 1.24, 0.905, 0.936 and 0.940 um of its wavelength ranges. Verification of MODIS precipitatble water is made using radiosonde data at 2 climatological stations in Java island (Jakarta and Surabaya). The result shows that the standard deviation between precipitable water which is derived by MODIS and radiosonde data (August-October 2004), is 1.6 cm, Meanwhile, through the statistical analysis, they have significant correlation of about 0.82. In adition, the relationship between the MODIS precipitable water and the altitude has a negative correlation (r= -0.98). It means that the precipitable water tends to decrease along with the increase of altitude, According to the climate condition in West Java which is mostly wetter rather than of East Java, we knew that the precipitable water in West Java is higher than East Java. Related to related to relative humidity, the mODIS precipitable water can be used to estimate relative humidity, based on topography area, the correlation coeficient between 0.84-0.92.